1985
DOI: 10.1073/pnas.82.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of the evidence for paramagnetism in oxy- and carbonmonoxyhemoglobins.

Abstract: Experiments have been carried out in an attempt to confirm previous reports of paramagnetism in the oxy-and carbonmonoxy derivatives of human and carp hemoglobin. When care is taken to ensure complete saturation of the hemoglobins with ligand and the diamagnetic contributions of all of the buffers are carefully evaluated, these hemoglobin derivatives are found to have the same gram susceptibilities as exhibited by a set of metal free proteins, suggesting that they are fully diamagnetic.In previous articles (1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
44
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 6 publications
4
44
0
1
Order By: Relevance
“…Note that it has been shown that a variety of nonparamagnetic metal-containing and metal-free proteins exhibit the same value of g ϭ -0.587 ϫ 10 -6 mL/g (30). With the use of Eq.…”
Section: Theoretical Model For Magnetic Susceptibility Of Whole Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that it has been shown that a variety of nonparamagnetic metal-containing and metal-free proteins exhibit the same value of g ϭ -0.587 ϫ 10 -6 mL/g (30). With the use of Eq.…”
Section: Theoretical Model For Magnetic Susceptibility Of Whole Bloodmentioning
confidence: 99%
“…[1], Y is the fraction of hemoglobin that is present in the form of oxyHb, n Hb is the total intracellular Hb concentration, 5.5 ϫ 10 -6 mol/mL (29), and g,protein is the gram susceptibility, diamagnetic contribution of the Hb protein which is equal to -0.587 ϫ 10 -6 mL/g (30). Other parameters included in the above equation are the volume susceptibility of water, H2O ϭ -0.719 ϫ 10 -6 (31), the molecular weight of deoxyHb, M Hb ϭ 64,450 g/mol (32) and the molar volume of Hb in solution, MHb ϭ 48,277 mL/mol (28).…”
Section: Theoretical Model For Magnetic Susceptibility Of Whole Bloodmentioning
confidence: 99%
“…Here, 0:587 Â 10 À6 mL=g is the mass susceptibility of globin relative to vacuum in CGS units (53,54); 4p is the unit conversion from CGS to SI units; and À9035 ppb is the water volume susceptibility relative to vacuum (55). X p ¼ À37:7 ppb is the oxyhemoglobin and blood plasma volume susceptibility (12).…”
mentioning
confidence: 99%
“…Pauling insisted that this result could not be correct (39), as did others (40), but the Italian group reported additional experiments at room temperature in support of their model (41). In 1985, however, Cerdonio threw in the towel (42). One of us (H.B.G.)…”
mentioning
confidence: 99%